A study of product strategy priorities at the small enterprises of the North-Alföld Region - Magyar, Zoltán (Acta Agraria Debreceniensis, 2009)
Through a non-representative sample of the small enterprises of the North-Alföld Region, this paper studies the product strategic priorities enabling us to make a detailed typology of small enterprises. According to the relevant technical literature, the types of small enterprises have typical strategic priorities. Obviously, each group can be characterised with certain strategic priorities, which are sharply distinct from each other. These priority features are shown in the form of characteristic features in the enterprise’s marketing activities, market behaviour (product policy, innovation attitude, technology, price policy). This paper studies the enterprises of the sample through the role of production technology, material quality, low price and branding endeavours affecting product positioning.